Surau dan Modernisasi Pendidikan di Masa Hindia-Belanda - Muhammad Rajab; Wandi Afrio Putra (UIN Imam Bonjol Padang, 2022)
Surau is a cultural heritage building of the local community before the advent of Islam. The surau is intended to function as a place to meet, gather for meetings and a place to sleep for boys who have reached puberty and parents who are old. With the arrival of Islam, surau also underwent an Islamization process. In addition to the above functions, its function was later expanded to become a place for teaching and developing Islamic teachings such as learning the Koran, places for ceremonies related to religion, places for mysticism, places for meetings, lodging. travelers, places of worship, bergambus and others. However, the function of the surau began to fade since the early 20th century which was marked by the arrival of the Dutch to West Sumatra with a situation squeezed by Dutch colonial economic-political pressures and reconditioned religion. The aims of the research include knowing the surau and the modernization of education during the Dutch East Indies era. The preparation of the research used the Library Research method. Data collection was carried out by means of a Literature Study. Data analysis was carried out by analyzing the contents of the book, related literature, historiography. From the results of the research conducted, it can be obtained the results of the research that the existence of the surau as one of the first Islamic educational institutions in Minangkabau had made efforts to modernize amid the penetration of the Dutch East Indies. The modernization referred to concerns an institutional system that is more accommodating to the demands of the development of Muslim society. The modernization of the surau was marked by the establishment of modern Islamic educational institutions, such as the Adabiyah School, Sumatra Thawalib, Madrasah Diniyah and so on which were the forerunners of the Jembatan Besi surau. Models of educational institutions use a curriculum that does not only teach religious education, but also includes general subjects. Furthermore, the development of organizations in the field of education originating from this surau further modernized the surau as an educational institution. The incessant penetration of the Dutch East Indies government into the existence of Islamic educational institutions in the Minangkabau area, apparently did not dampen the enthusiasm of the ulama with the consolidation carried out with Islamic reformers who were increasingly showing their stability.